Pengaruh lama waktu penggorengan (frying pan) terhadap kadar lemak ikan seluang (Rasbora sp.) - Ambeng, Qeyla Resido; Yuliani, Ni Nyoman Sri; Balyas, Abi Bakring (Barigas: Jurnal Riset Mahasiswa, 2024)
According to WHO, there are 4 main factors that influence incidence of stunting, namely maternal and environmental factors, barriers to breastfeeding, infection factors, and complementary feeding factors. Fat is one of nutrients that affect growth and development of children and found in many foodstuffs, one of which is Seluang fish. Nutritional content contained in fresh seluang fish per 100 g consists of 47.54 mg protein, 12.36 mg fat, 21.53 kilo calories, 2.9 ppm iron, 0.38 ppm copper, and 3.64 zinc ppm. This study aims to determine the effect of frying time on fat content of fish and to determine best length of time that can maintain fat content in seluang fish. This study uses experimental research methods. Design used in this study was completely randomized study design, object in form of seluang fish was treated by frying it with three different types of times. There is a difference in fat content between the frying time of 7.5 minutes, 8 minutes and 8.5 minutes with value of p = 0.004 (<0.05). There is an effect of length of frying time on fat content of seluang fish (p <0.05). The best length of time that can maintain the fat content in Seluang fish is 7.5 minutes.